The Effectiveness of Google Classroom Media in Teaching English for Tourism at a Tourism and Business Institute - Ni Komang Arie Suwastini; I Made Drati Nalantha; Gede Rasben Dantes (IJEE (Indonesian Journal of English Education), 2021)
ABSTRACTThe present study examined the effectiveness of Google Classroom media in teaching English for tourism students at a private Tourism and Business Institute in Bali during mandatory online learning in 2020. The study was qualitative research, implementing the QAIT model for evaluating the effectiveness of Google Classroom in teaching English, involving four lecturers and 42 students. The data were collected through observations of the teaching-learning process in two classes and interviews with the lecturers. The researchers were the primary research instrument, supported by interview guides and an observation checklist. In general, the use of Google Classroom in these English for Tourism classes was only sufficiently effective, with only one lecturer performing well, two lecturers performing sufficiently, and one lecturer performing insufficiently. Obstacles identified among the students were lousy internet connection, lack of device, low motivation, and lack of readiness in using the online learning platform. In conclusion, the implementation of Google Classroom in the observed English Classroom was proven to be only sufficient. This conclusion implies the need for more training for teachers in using Google Classroom to improve the quality, appropriateness, incentive, and time-effectiveness of the teaching and learning process, especially in online learning. ABSTRAKPenelitian ini mengamati efektivitas media Google Classroom dalam pengajaran bahasa Inggris untuk mahasiswa pariwisata di Institut Pariwisata dan Bisnis swasta di Bali selama pembelajaran online wajib tahun 2020. Penelitian ini adalah penelitian kualitatif, mengimplementasikan model QAIT untuk mengevaluasi efektivitas Google Classroom di pengajaran bahasa Inggris, yang melibatkan empat dosen dan 42 mahasiswa. Pengumpulan data dilakukan melalui observasi proses belajar mengajar di kedua kelas dan wawancara dengan dosen. Peneliti bertindak sebagai instrumen penelitian utama, didukung oleh pedoman wawancara dan daftar periksa observasi. Secara umum penggunaan Google Classroom pada kelas Bahasa Inggris untuk Pariwisata ini baru cukup efektif, dengan hanya satu dosen yang berprestasi baik, dua dosen berprestasi cukup, dan satu dosen dirasa kurang memadai. Kendala yang ditemukan pada siswa adalah koneksi internet yang buruk, kurangnya perangkat, motivasi yang rendah, dan kurangnya kesiapan dalam menggunakan platform pembelajaran online. Kesimpulannya, penerapan Google Classroom di Kelas Bahasa Inggris yang diamati terbukti hanya cukup. Kesimpulan ini menyiratkan perlunya lebih banyak pelatihan bagi guru dalam menggunakan Google Classroom untuk meningkatkan kualitas, kesesuaian, insentif, dan efektivitas waktu proses belajar mengajar, terutama dalam pembelajaran online.